Otimização de protocolo de estabelecimento in vitro de duas cultivares de oliveira - Santos, Jullie dos (2018)
The wide consumption of olive products, table olives and olive oil have shown that the species has a high potential, attracting the interest of national and international producers. For this, plant tissue culture is a viable technique for the production of seedlings in short time and space, guaranteeing homogeneity and phytosanitary quality of the plants produced, besides being an opportunity to improve the processes of genetic improvement and propagation of this species. However, woody plants like the olive tree present difficulties in the in vitro establishment due mainly to the contamination and oxidation, which makes it necessary to adopt efficient techniques of asepsis and control of the oxidation of explants under these conditions. The objective of the first experiment was to develop an in vitro establishment protocol from nodal segments of two olive cultivars desinfestation different concentrations of sodium hypochlorite isolated in WPM medium supplemented with different concentrations of BAP (6-benzylaminopurine). The experiment was conducted on completely randomized design, in a triple factorial scheme (2x3x3), two olive cultivars (Arbequina and Koroneiki), three concentrations of sodium hypochlorite for the decontamination of the explants (0,6; 0,8 and 1,0% active chlorine) and three BAP concentrations (0,00; 2,22 e 4,44 μM) totalizing 18 treatments. According to the results, it was possible to observe that the treatments tested in this experiment were not efficient in the in vitro establishment of olive cv. Arbequina, however the concentration of 2,22 μM of BAP and the concentration of sodium hypochlorite 1 % active chlorine, used in disinfestation of the explants, are ideal for the in vitro establishment of olive cv. Koroneiki. The second experiment objected evaluate the effects of different antioxidant agents in the in vitro establishment of olive cvs. Koroneiki and Arbequina. The experiment was conducted on completely randomized design, in factorial scheme (2x6), two olive cultivars (Arbequina and Koroneiki), three concentrations of sodium hypochlorite for the decontamination of the explants (0,6; 0,8 and 1,0% active chlorine), totalizing 12 treatments. The results at 21 days after isolation allowed to conclude that cultivar Arbequina is less susceptible to oxidation compared to Koroneiki and the antioxidant ascorbic acid at the concentration of 1 g L-1 was shown to be efficient in controlling the oxidation of olive explants cvs. Arbequina and Koroneiki.